1997
DOI: 10.1890/1051-0761(1997)007[0702:cwdaaf]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Coarse Woody Debris as a Function of Age, Stand Structure, and Disturbance in Boreal Newfoundland

Abstract: We examined the structural attributes of coarse woody debris (CWD) in balsam fir and mixed balsam fir‐black spruce forests in western and central Newfoundland. The purpose of the study was to document CWD abundance and structure within various stages of stand development, and to generate simple models to predict CWD availability as habitat for forest wildlife. Our objectives were threefold: (1) determine the temporal patterns of CWD following clear‐cut disturbance, and compare these second‐growth stands to old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
97
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(117 citation statements)
references
References 19 publications
17
97
2
1
Order By: Relevance
“…We demonstrated that tree biomass C storage exhibited an S-shape growth trend (Figure 3b), which is consistent with other studies on the relationship between live biomass and stand age [24,34,35]. Mature forest stand had relatively higher production of plant debris than younger plantations [15,36]. In addition, because the C storage of woody debris was persistent and slow to break down [8,9,37], its decomposition rate should be lower than that of litter.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We demonstrated that tree biomass C storage exhibited an S-shape growth trend (Figure 3b), which is consistent with other studies on the relationship between live biomass and stand age [24,34,35]. Mature forest stand had relatively higher production of plant debris than younger plantations [15,36]. In addition, because the C storage of woody debris was persistent and slow to break down [8,9,37], its decomposition rate should be lower than that of litter.…”
Section: Discussionsupporting
confidence: 88%
“…However, this proportion is substantially lower than that of temperate forests in other regions of the world (8-47%) [44][45][46][47]. Numerous factors, e.g., forest structure, stand age, site productivity, decomposition rate and disturbance regime, may influence the accumulation of plant debris [5,15,48]. The large discrepancy of plant debris C storage and the relative contribution to ecosystems from these forests in northeastern China and those of similar forest types in other regions of the world may be derived not only from the variability in ecosystem development but also from the difference in stand history and disturbance regime.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we considered that the "U" shape pattern was also to be found in the tree mortality. The same "U" shape pattern was also observed by other studies described in References [27,58,59].…”
Section: Discussionsupporting
confidence: 88%